Asymmetries of vestibular dysfunction in major depression - Ried, A.M. Soza; Aviles, M. (Neuroscience, 2007)
Depression is characterized by alterations in the circadian secretion of hormones, sleep and motor activity, all of which are regulated by suprachiasmatic nuclei (SCN). The vestibular system in the inner ear registers the amount of motor activity. To test the integrity of this motion sensitive system in depression, we studied the vestibulo-ocular reflex (VOR) in depressive patients who were not taking medication and healthy control subjects, which allowed us to investigate each ear and its corresponding nerve centers. Ocular reflex movement depends on vestibular nuclei activity, and we found that at 30 °C stimulation the right vestibular system in depressive patients has approximately half the activity of the left side. Significant asymmetry was not detected in control subjects. We also found a significant decrease in the slow phase (16.92±9.13°/s) of the reflex in the depressed group as compared with the control group (43.77±16.04°/s). The vestibular nuclei of the right and left sides are hypoactive. Specifically, the right vestibular nucleus is hypoactive in depressed people and can easily be measured using VOR. These results support the abnormal asymmetries hypothesis of depression and suggest that these asymmetries also exist at the level of the brain stem or neuronal centers that are afferents to right vestibular nuclei, like SCN or raphe nuclei.